Inclination of young maize farmers to practice climate-smart agriculture (2022)
Dependency on rainfall and other climatic factors have exposed farmers to various climate risks. To reduce the effect of climate risk, various climate change adaptive strategies have to be employed including climate-smart agricultural practices. Hence, the study researched the inclination of youth maize farmers to practice climate-smart agriculture. A total of 120 maize farmers were selected in Ogun State, Nigeria through a multi-stage sampling procedure. Data was obtained using a structured questionnaire and interview schedule. The data were described using frequency counts, mean, percentages and ranks. Chi-square and PPMC analyses were used to test the relationship between independent variables and dependent variable. The result shows that most (83.3%) of the respondents rented land used for farming, with a mean farm size of 7.90 ± 9.98 acres and mean years of farming experience of 16.21±9.53 years. Fellow farmers ((x=1.22) were the main source of information on climate smart agricultural practices. There was high level (70.8%) of knowledge of climate smart agriculture. Channel of information for climate change information (x=1.44) and high labour cost x=1.41) ranked first of constraints to practice climate smart agriculture. Willingness (70.8%) to practice climate smart agriculture was high. There was a significant relationship between respondents’ source of labour (χ2=6.001, p< 0.05), farm size (r= 0.338, p<0.05) and inclination to use climate-smart agricultural practices. The study concludes that young farmers involved in maize production are willing to practise climate smart agriculture. Extension agents from government and non-governmental organizations should adopt e-extension for disseminating climate- smart agricultural practices to young farmers.